2017
DOI: 10.1039/c7ra05864k
|View full text |Cite
|
Sign up to set email alerts
|

A new adsorbent of Pb(ii) ions from aqueous solution synthesized by mechanochemical preparation of sulfonated expanded graphite

Abstract: After the mechanochemical modification, sulfonated functional groups were able to be attached on the surface of SEG effectually, acted a significant role in the adsorption process, the schematic diagram of SEG interacted with Pb(ii) showing as below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Jin et al . confirmed that MnO 2 -loaded EG displayed high removal efficiency on Cr(VI) [27], and in our previous study, sulfonated EG was prepared via mechanochemical treatment to adsorb Pb (II) in aqueous solution [28]. In addition, to achieve a noteworthy enhancement on the stability and mobility of nZVI, a variety of carbonaceous materials, like carboxymethyl cellulose [29], carbon nanotube [30] and tubular nitride carbon [31] were applied as the substrate for better attachment.…”
Section: Introductionsupporting
confidence: 57%
“…Jin et al . confirmed that MnO 2 -loaded EG displayed high removal efficiency on Cr(VI) [27], and in our previous study, sulfonated EG was prepared via mechanochemical treatment to adsorb Pb (II) in aqueous solution [28]. In addition, to achieve a noteworthy enhancement on the stability and mobility of nZVI, a variety of carbonaceous materials, like carboxymethyl cellulose [29], carbon nanotube [30] and tubular nitride carbon [31] were applied as the substrate for better attachment.…”
Section: Introductionsupporting
confidence: 57%
“…Therefore, chemical composition analysis was carried out by XPS to monitor the changes in the chemical composition on the surface of the hybrid EG additives compared to neat silica and EG. Survey scans of EG, represented in Figure 2a, show two main peaks of C1s and O1s at 286 and 534 eV, respectively, indicating the presence of the carbon and oxygen content [30]. According to the XPS results tabulated in Table 4, EG contains 98% of carbon and 2% of oxygen in its structure, which makes it an excellent candidate for the enhancement of higher thermal conductivity than other carbon-based materials [31].…”
Section: Structural Properties Of Functionalized Silica and Silica-momentioning
confidence: 99%
“…The broad XRD peak on the pattern of silica appeared at around 2θ = 21°, belonging to (101) planes, revealing the amorphous structure of the silica [36], and the peak that appeared at around 2θ = 43.6° belongs to the metallic holder. EG shows a sharp peak at around 2θ = 26.5° belonging to the diffraction of (002) planes and a smoother peak at around 2θ = 54.6° belonging to the diffraction of (004) planes, indicating a crystalline structure [30]. As seen in Table 5, after the attachment of the silica particles on the EG surface, the crystallinity degree of EG decreases from 89% down to 70.6% and 68.7% in H-EG-1 and H-EG-2, respectively.…”
Section: Structural Properties Of Functionalized Silica and Silica-momentioning
confidence: 99%
“…Only two intense and distinct peaks at around 283.8 and 531.3 eV were observed, which were attributed to the high purity of the graphite, corresponding to the C 1s and O 1s peaks, respectively. 34 Furthermore, the other weak peaks at approximately 151.1 eV could be related to Si 2s caused by a tiny amount of impurity. 35 On the basis of the results obtained via XPS for the surface atomic concentration, the mass ratio of C and O could be obtained and reected the existence of other oxides.…”
Section: Characterization Of the Various Graphitesmentioning
confidence: 99%